2017
DOI: 10.1177/1073191116685401
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Brief Version of the Posttraumatic Cognitions Inventory (PTCI-9)

Abstract: Negative posttraumatic cognitions lead to the development and maintenance of posttraumatic stress disorder symptoms. There is a need for a brief measure to assess these cognitions. Participants were administered the Posttraumatic Cognitions Inventory (PTCI) and measures of mental health symptomatology. These data were used to develop a brief version of the PTCI (PTCI-9) in 223 male and female veterans, which was then examined in a sample of 117 female civilians. Confirmatory factor analyses demonstrated an acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
1
41

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(122 citation statements)
references
References 70 publications
9
71
1
41
Order By: Relevance
“…PTCI-9 total and subscale scores display good internal consistency and strong correlations with the PTCI-36 (Foa, Ehlers, Clark, Tolin, & Orsillo, 1999). Previous findings demonstrated that the PTCI-9 is a reliable and valid measure of posttraumatic cognitions (Wells et al, 2019).…”
Section: Posttraumatic Negative Cognitionsmentioning
confidence: 82%
“…PTCI-9 total and subscale scores display good internal consistency and strong correlations with the PTCI-36 (Foa, Ehlers, Clark, Tolin, & Orsillo, 1999). Previous findings demonstrated that the PTCI-9 is a reliable and valid measure of posttraumatic cognitions (Wells et al, 2019).…”
Section: Posttraumatic Negative Cognitionsmentioning
confidence: 82%
“…Furthermore, post-traumatic disruption in one's self-concept was found to be associated with depression regardless of cultural group or clinical status. These findings indicate depression to be a common post-traumatic reaction following a trauma or highly stressful life event and is not necessarily unique to PTSD (Wells et al, 2017). Researchers and clinicians would benefit from considering how these factors may contribute to depressive sequalae, for instance targeting a trauma-defined or distorted self-image could reduce negative self-evaluations and foster positive adaptation.…”
Section: Discussionmentioning
confidence: 93%
“…Maximally 90-minute sessions will be held two times a week and will be provided within the mental health organization where the participant receives his or her usual care. rating), 46 avoidance (2 items, 0 -4 rating), 46 negative cognitions and mood (7 items, 0 -4 rating), 46 hyper arousal (6 items, 0 -4 rating), 46 beliefs about self/beliefs about others (9 items, 1-7 rating), 47 dissociation (4 items, 0 -4 rating), 48 control (3 items, 1 -7), 49 involuntary memory characteristics (7 items, 1 -7 rating), 60 and hallucinations (3 items, 1 -7 scale) and paranoia (3 items, 1 -7). 50,51…”
Section: Treatment Of Subjectsmentioning
confidence: 99%
“…This is a 9-item version is based on the original PTCI 65 and was found to have strong psychometrics. 47…”
Section: Psyratsmentioning
confidence: 99%
See 1 more Smart Citation